2011
DOI: 10.1016/j.foodres.2010.10.039
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional constituents and antioxidant properties of indigenous kembayau (Dacryodes rostrata (Blume) H. J. Lam) fruits

Abstract: The nutritional and antioxidant properties of peels, pulp and seeds of kembayau (Dacryodes rostrata) fruits were evaluated. Kembayau seeds and pulp were rich in fat, while peels had the highest ash contents. Potassium was the most prevalent mineral in peels (380.72-1112.00 mg/100 g). In kembayau fruits, total flavonoid content (1012.74-28,022.28 mg rutin equivalent/100 g) was higher than total phenolic and total monomeric anthocyanin contents. Kembayau seeds exhibited high flavonoid and phenolic contents compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 18 publications
3
21
1
Order By: Relevance
“…caffra and H. caffrum, found percent RSA values varying from 2.5 up to 27.2. Some exotic fruits have high RSA (Kong et al, 2011), such as indigenous kembayau (Dacryodes rostrata (Blume)) fruit, with seeds (92.18-92.19%), pulp (91.47-92.15%) and peels (70.39-86.51%), with the seeds showing the highest amount of total flavonoids and phenolics. Ribeiro, Barbosa, Queiroz, Knödler, and Schieber (2008) showed that the DPPH radical-scavenging capacity of peel and seed kernel extracts of the mango variety Ubá was concentration-dependent (1000-5000 ppm).…”
Section: Total Phenolic Content (Tpc) Antioxidant Assays and Ascorbimentioning
confidence: 99%
“…caffra and H. caffrum, found percent RSA values varying from 2.5 up to 27.2. Some exotic fruits have high RSA (Kong et al, 2011), such as indigenous kembayau (Dacryodes rostrata (Blume)) fruit, with seeds (92.18-92.19%), pulp (91.47-92.15%) and peels (70.39-86.51%), with the seeds showing the highest amount of total flavonoids and phenolics. Ribeiro, Barbosa, Queiroz, Knödler, and Schieber (2008) showed that the DPPH radical-scavenging capacity of peel and seed kernel extracts of the mango variety Ubá was concentration-dependent (1000-5000 ppm).…”
Section: Total Phenolic Content (Tpc) Antioxidant Assays and Ascorbimentioning
confidence: 99%
“…Owing to its hard texture, DR fruit is normally consumed after blanching with hot water by the local people. It is also preserved using salts or black soya sauce and taken as an accompaniment of rice or porridge (Kong et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In recent year a search for new edible plant species with healthenhancing properties prompted interest in indigenous fruits (Puente, Pinto-Munoz, Castro, & Cortes, 2010;Kong et al, 2010) and native Australian fruits should be considered as a valuable source. The number of native fruiting plants growing in tropical forests of Australia that have the potential to be developed into exotic fruits for consumers around the world exceeds 2000.…”
Section: Introductionmentioning
confidence: 99%